Pengelolaan Badan Usaha Milik Desa (BUMDes) Desa Sungai Geringging Kecamatan Kampar Kiri Kabupaten Kampar - Jas, Rafis Fajri; Khairul Amri (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Village development is a priority in national development, so what can be done in village development is to find the root of the problems that have been experienced by village communities. To achieve national development goals, the village is the leading government agency that can reach target groups who wish to prosper, in an effort to improve people's welfare, namely by forming a business entity, namely the Village-Owned Enterprise (BUMDes) which is a business institution whose goal is to help economic enterprises. villages so that they can add PADes. This study aims to determine the Management of Geringging Joint Village Owned Enterprises (BUMDes) in Sungai Geringging Village, Kampar Kiri District, Kampar District, and to determine the factors that hinder the Geringging Joint BUMDes Management, Sungai Geringging Village, Kampar Kiri District, Kampar District. The theory used in this research is management theory by George R. Terry. This type of research is descriptive qualitative with data collection techniques of interviews, observation and documentation. Based on the research results, it can be seen that the management of the Geringging Village Owned Enterprise (BUMDes) in Sungai Geringging Village, Kampar Kiri District, Kampar Regency, has not run optimally yet. Then the factor that becomes an obstacle to the management of BUMDes Geringging with the village of Sungai Geringging is the lack of human resources.